Presence of pro-lentiviral DNA in male sexual organs and ejaculates of small ruminants - Peterson, K.; Brinkhof, J.; Houwers, D.J.; Colenbrander, B.; Gadella, B.M. (Theriogenology, 2008)
To be able to predict sexual transmissibility of small ruminant lenti viruses (SRLV), it is necessary to know whether or not the virus is excreted in the semen, and under what circumstances. Thus, this research focussed on establishing the presence of proviral DNA of SRLV in semen and in the male genital tract of small ruminants. After initial results established the presence of SRLV in serum, the emergence of proviral DNA of SRLV in semen and presence in blood in a group of naturally SRLV-infected individuals (13 rams and 4 bucks), was followed temporally using real-time polymerase chain reaction (PCR). The same animals were also systematically serologically monitored by enzyme-linked immuno sorbent assay (ELISA) during the breeding season (August–February). A triple monocyte–macrophage count was performed on both blood and semen using a specific monoclonal antibody in conjunction with flow cytometry. The finding that epididymal semen and tissue samples of the testes, epididymides, ampullary, vesicular, prostate and bulbo-urethral glands all tested positive for the presence of proviral DNA indicates that various male sexual organs may contribute directly to shedding of proviral SRLV DNA in ejaculated semen. Our results suggest that small ruminants show intermittent shedding of proviral SRLV DNA into epididymal as well as ejaculated semen. They also demonstrate that a single PCR-negative semen sample cannot be used as a diagnostic tool to predict that subsequent ejaculates will be SRLV-free. No significant relationship was found between numbers of monocytes and/or macrophages in blood or semen and the detection of proviral SRLV in ejaculates.